Korelasi Pengetahuan Ecosophy dengan Perilaku Perempuan terhadap Sungai di Desa Sungai Rangas Tengah Kabupaten Banjar - Humairo, Faridah; Hamid, Ismar (Huma: Jurnal Sosiologi, 2024)
The Martapura River plays a vital role as a source of life for the community, especially for women, whose almost entire daily activities are related to the river, such as washing, bathing, and earning a livelihood. This study aims to examine the correlation between ecosophy knowledge and women's behavior in managing and utilizing the river. This study uses a quantitative survey method, conducted in Sungai Rangas Tengah Village, Banjar Regency. The study population consisted of women aged 20 to 80 years who have lived in Sungai Rangas Tengah Village, Banjar Regency for more than 10 years. The research respondents were 50 women randomly selected using a purposive sampling technique. The data analysis techniques used include descriptive, simple regression, and correlation. The results of the study show that a deep understanding of ecosophy is positively and significantly correlated with women's behavior towards the river. The higher the understanding of ecosophy among women, the higher the level of responsive behavior towards the river. The contribution of ecosophy to women's behavior towards the river is 49%, while the remaining 51% is influenced by other factors beyond ecosophy understanding. However, there is still a noticeable gap between conceptual understanding and daily practice. Although the majority of respondents are aware of the dangers and negative impacts of dumping waste into the river, technical constraints such as the lack of waste management facilities and inadequate waste disposal systems hinder the implementation of ecosophy ethics in daily life. It is crucial to have continuous efforts from related parties to enhance women's understanding of ecosophy, whether through education, training, or empowerment, as a crucial aspect in promoting environmentally friendly practices, especially in river environments.